Decision making styles of school administrators and the level of thrust of teachers in public elementary schools in the division of Bulacan - Faundo, Fe Fuentes (Bulacan State University research journal, 2012)
This research focused on the school administrators' decision making styles in terms of directive, behavioral, analytical, and conceptual and the level of trust of teachers in school administrators; colleagues and clients in selected public elementary schools in the Division of Bulacan for the SY 2009-2010. The study looked into personal demographic profile of the teachers to determine the level of trust on the performance of the school administrators. The decision making styles of school administrators was determined based on the Decision Style Inventory (by Rowe et. al, 1994), while The Omnibus T-Scale (by Hoy and Moran, 2003) instrument was used to measure the level of trust of teachers in school administrators, colleagues and clients. Decision making is the perennial challenge for the school administrator. The specific function of administration is to develop and regulate the decision making process of the most effective manner possible. According to Abad (2004), an effective decision making requires knowledge, interpersonal skills and technical skills, thus understand effective professional learning and how it can be put into practice as part of an overall strategy for school improvement. This will create organization conditions that would be conducive for teachers to continuously improve the teaching practices by providing encouragement and fostering an environment that builds trust as part of continuous development. In this study, the credibility of an administrator was given emphasis in terms of making decision; likewise; know what is expected of them, what goals they are reaching and what targets have to be met. The difference between an average administrator and a good one lies in the quality and credibility of its administration, influences also vary with the level of work done. For an effective administrator, important determinants include previous relevant education and experiences, values and views of work that govern the choices, behavior and aspirations of both the administrators and the teachers.